Strategi dan Gaya Komunikasi Dakwah Ustadz Adi Hidayat di Youtube serta Efeknya terhadap Publik - Nur Latifah (Al-INSAN Jurnal Bimbingan Konseling dan Dakwah Islam, 2024)
Ustadz Adi Hidayat is a famous Indonesian preacher who has high popularity among the public. Even though his name is not listed in the 200 recommended preachers from the Ministry of Religion (Ministry of Religion), he is still popular with the public because he actively preaches on social media, one of which is YouTube. With the rise of the phenomenon of preaching on social media, Ustadz Adi Hidayat has also expanded his preaching efforts through social media, one of which is YouTube because it is considered an effective medium for preaching in this technological era. In preaching, especially on YouTube, Ustadz Adi Hidayat has a strategy and communication style that can make people admire and like his preaching. Therefore, this research aims to describe the communication strategy and style of Ustadz Adi Hidayat's preaching communication and determine the effects that arise on viewers of his preaching videos on YouTube. This research is research with a type of qualitative descriptive analysis, namely research that prioritizes quality over quantity. The method used is the documentation and observation method with two types of data, namely primary data and secondary data. Primary data was obtained from several da'wah videos on Ustadz Adi Hidayat's YouTube channel. Meanwhile, secondary data was obtained from writings related to the strategy and communication style of Ustadz Adi Hidayat's preaching. The findings in the field stated that Ustadz Adi Hidayat preached by including verses from Allah SWT. Nor the hadith of the Prophet SAW. they also often hold studies discussing books and interpretations. Ustadz Adi Hidayat preaches more by analyzing issues that are currently developing in society. In preaching on YouTube. Ustadz Adi Hidayat is very calm and friendly. With the strategy and communication style presented by Ustadz Adi Hidayar, many people saw their preaching videos so that many people who initially did not know became aware of what the two ustadz were conveying. In fact, many people expressed their desire to follow what Ustadz Adi Hidayat conveyed in his preaching on YouTube.